Peran Akun Demo PT Trijaya Pratama Future dalam Edukasi Trading Mahasiswa - Kurniawan, Syahrul; Santoso, Bowo (Universitas Pahlawan Tuanku Tambusai, 2026)
The increasing interest of students in trading as part of financial literacy requires a safe and structured learning approach. This community service activity aims to enhance students’ basic understanding of trading through the use of TPFx demo accounts as a risk-free educational tool. The methods applied include socialization, training on the MetaTrader platform, and guided trading practice using demo accounts. The activity involved students of UPN Veteran Jawa Timur with diverse levels of trading knowledge. The results indicate an improvement in participants’ understanding of risk management, chart analysis skills, and awareness of trading psychology. Furthermore, the use of demo accounts increased students’ confidence in understanding market mechanisms before engaging in real trading. This activity demonstrates that demo accounts play an effective role as an initial trading education medium for students.